Black and White Rabbits ABC - Baker, Alan, 1951- (New York : Kingfisher, 2017)
The story of a rabbits exhausting efforts to paint a picture presents the letters of the alphabet.
Keywords: Alphabet -- Fiction; Rabbits -- Fiction; Painting -- Fiction